Genetic analysis of ERBB4 gene in Chinese patients with amyotrophic lateral sclerosis: a single-center study and systematic review of published literature - Shen, Dongchao; Yang, Xunzhe; He, Di; Zhang, Kang; Liu, Shuangwu; Sun, Xiaohan; Li, Jinyue; Cai, Zhengyi; Liu, Mingsheng; Zhang, Xue; Liu, Qing; Cui, Liying (Frontiers in Aging Neuroscience, 2025)
BackgroundRare ERBB4 variants have been implicated in amyotrophic lateral sclerosis (ALS), but their prevalence and clinical significance remain poorly understood, particularly across different ethnic populations.MethodsWe performed genetic screening of ERBB4 in 1627 Chinese ALS patients using whole-exome sequencing. A systematic review and meta-analysis of the published literature were conducted to evaluate the global frequency of ERBB4 variants and their clinical correlations.ResultsWe identified 14 missense variants and 6 splice region variants in 23 unrelated patients, with four variants classified as damaging (p.R782P, p.M799T, p.R847C, and p.S997R). The splice variant c.1490-3C > T, associated with a 50% reduction in ERBB4 mRNA expression, was maternally inherited by a male ALS patient, while its presence in his asymptomatic mother suggests the involvement of potential genetic modifiers. ERBB4 variant carriers demonstrated earlier disease onset compared to non-carriers (46.9 ± 10.3 vs. 52.6 ± 11.2 years; p = 0.015), though survival duration remained comparable. Meta-analysis revealed a pooled ERBB4 variant frequency of 0.83% (95% CI, 0.56–1.10%) in ALS patients globally, with notable ethnic differences (1.36% in Chinese, 0.66% in European, and 1.44% in American populations).ConclusionOur findings establish the prevalence of ERBB4 variants in ALS across different populations and suggest their potential role as disease modifiers, particularly affecting the age of onset. The ethnic variation in mutation frequency highlights the importance of population-specific genetic screening strategies in ALS.